Comparative advantage and caste evolution. (1st March 2020) - Cole, Blaine J.
Abstract: Most of the theory for the evolution of caste specialization in social insects assumes that increased efficiency in worker labor leads to specialization and increased worker efficiency gives colonies with behavioral specialists an advantage. However, there are an increasing number of studies that show that the task specialists within social insect colonies do not have the highest efficiency. Indeed, some studies show that some groups of workers are uniformly better than all other groups at every task. In this note, I adapt the principle of comparative advantage from economics to show that, rather than maximizing the payoff, specialization is advantageous when minimizing opportunity costs. This leads to the prediction that caste specialization should be associated with reduced opportunity costs rather than increased task efficiency.